Cervantes and the early modern mind. - Jaén, Isabel, 1970-; Simon, Julien Jacques, 1974- ([Place of publication not identified] : Routledge, 2017)
This book explores the work of Cervantes in relation to the ideas about the mind that circulated in early modern Europe and were propelled by thinkers such as Juan Luis Vives, Juan Huarte de San Juan, Oliva Sabuco, Andrs Laguna, Andrs Velsquez, Marsilio Ficino, and Gmez Pereira. The editors bring together humanists and scientists: literary scholars and doctors whose interdisciplinary research integrates diverse types of sources (philosophical and medical treatises, natural histories, rhetoric manuals, pharmacopoeias, etc.) alongside Cervantes's works to examine themes and areas including emotion, human development, animal vs. human consciousness, pathologies of the mind, and mind-altering substances. Their chapters trace the cognitive themes and points of inquiry that Cervantes shares with other early modern thinkers, showing how he both echoes and contributes to early modern views of the mind.
Keywords: Cervantes Saavedra, Miguel de, -- 1547-1616 -- Criticism and interpretation; Cognition and culture; Literature and science; LITERARY CRITICISM / European / Spanish & Portuguese; PSYCHOLOGY / Cognitive Psychology